2015
DOI: 10.1016/j.yfrne.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Developmental influences on circuits programming susceptibility to obesity

Abstract: Suboptimal maternal nutrition exerts lasting impacts on obesity risk in offspring, but the direction of the effect is determined by the timing of exposure. While maternal undernutrition in early pregnancy is associated with increased body mass index, in later pregnancy it can be protective. The importance of the timing of maternal undernutrition is also observed in rodents, however, many of the processes that occur in the last trimester of human gestation are delayed to the postnatal period. Neonatal leptin ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 163 publications
(287 reference statements)
4
33
0
Order By: Relevance
“…These data are consistent with numerous studies showing that maternal exposure to environmental stressors exerts long-term energy metabolic effects on offspring through programming of hypothalamic circuits regulating energy balance [21]. Further studies are undergoing to identify the structural and/or functional alterations in the hypothalamus that may account for the decreased expression of NPY and food intake.…”
Section: Discussionsupporting
confidence: 89%
“…These data are consistent with numerous studies showing that maternal exposure to environmental stressors exerts long-term energy metabolic effects on offspring through programming of hypothalamic circuits regulating energy balance [21]. Further studies are undergoing to identify the structural and/or functional alterations in the hypothalamus that may account for the decreased expression of NPY and food intake.…”
Section: Discussionsupporting
confidence: 89%
“…In some cases it has been shown that genes involved in the thermoregulatory response are direct targets of circadian clock transcription factors 32 . The current analysis indicates that the light-OPN3 pathway is required for development of the thermosensory response 28 . We have shown the light-OPN3 pathway regulates Leptin , an adipokine implicated in this aspect of development.…”
mentioning
confidence: 72%
“…Furthermore, Opn3 null mice show low “brite” adipocyte content in inWAT and abnormal mitochondrial morphology in iAT. In neonatal mice, Leptin , found at low levels in Opn3 null mice, is required for establishing the thermogenesis circuit 28 . The TRP channels that cluster in transcriptome analysis of the Opn3 null, function as thermosensors 29 .…”
mentioning
confidence: 99%
“…The impact of fetal adipocytokines on growth and obesity risk during childhood is unclear. Evidence from animal studies has suggested that fetal leptin and adiponectin exposure induces changes in hypothalamic circuits and adipose tissue deposition, respectively, which may in turn increase offspring adiposity . Fewer studies have quantified the association between fetal adipocytokines and growth (i.e., change in anthropometry over time), and the results have been inconclusive .…”
Section: Introductionmentioning
confidence: 99%